Patho-physiological Mechanisms Involved in Abdominal Compartment Syndrome - Leonardo Javier Pérez Ponce; Roberto Carlos Barletta Farías; Gabriela Castro Vega; Jorge Bárbaro Barletta Farías; Fausto Castillo Franco; Jorge Emilio Barletta del Castillo (Revista Finlay)
Intra-abdominal hypertension and compartment syndrome are frequent entities in severely ill patients and result in a high mortality. This work is aimed at explaining the ethiopathogenesis of compartment abdominal syndrome, so as describing pathophysilogical mechanisms involved in this pathology. For that, a total of 25 bibliographic resources were reviewed, among them journals, books and others, consulted through the main information agents. It was concluded that the compartment syndrome is caused by the decrease of the abdominal wall distensibility and the increase of intraabdominal volumen or a combination of both. In addition it is produced by the direct organ compression by intra-abdominal hypertension, edema, ischemia secundary to blood flow decreasing, disturbances of the function and composition of the intestinal microbiota, all which later causes a multiple organ disfunction.